The influence of properties of different brands of fuel for diesel engine on characteristics of fuel feedinG - V. R. Vedruchenko; V. V. Krainov; P. V. Litvinov (Вестник СибАДИ, 2017)
The analysis of the influence of the basic physical properties of the different brands of fuels for diesel engine for fuel feed processing in high pressure systems. It shows the effect of fuel properties on the indicator chart by indexing experiment. We offer the most effective solutions, allowing diesel fuel to ensure stable performance when using fuels with different properties.